Kant and Theodicy a Search for an Answer to the Problem of Evil - Huxford, George (Lexington Books, 2020)
Kant was engaged with the subject of theodicy throughout his career and not merely in his 1791 treatise explicitly devoted to the subject. George Huxford traces Kant's thought on theodicy throughout his career to show not only the continuity of Kant's consideration but also his philosophical development on the subject.